An Overview of Asthma and COVID-19: Protective Factors Against SARS-COV-2 in Pediatric Patients - Liuzzo Scorpo, Maria; Ferrante, Giuliana; La Grutta, Stefania (Frontiers in Pediatrics, 2021)
Coronavirus disease 2019 (COVID-19) is a pandemic infectious disease caused by severe acute respiratory syndrome coronavirus SARS-COV-2. Aberrant innate immunity response and cytokine storm are responsible for the syndrome. Apparently, in asthmatic patients, the inadequate antiviral immune response and the tendency for asthma exacerbation evoked by common respiratory viruses could explain increased susceptibility to SARS-COV-2 infection. However, asthma has not been suggested to be a risk factor in COVID-19 patients. Therefore, in asthmatic patients some potential protective mechanisms against SARS-COV-2 have been hypothesized, like type 2 immune response, number of eosinophils, overproduction of mucus, and asthma treatment, along with behavioral factors not strictly related to asthma, such as social distancing, hygiene measures and wearing facemasks, that contribute to reduce the individual susceptibility to SARS-COV-2 infection. In this mini-review, we will describe the current literature regarding potential protective factors against COVID-19 in children with asthma based on the evidence available so far.